Violência filho-parental sob a perspectiva de adolescentes - Sturnichi, Felipe Moreira (Universidade Federal de São Carlos)
Child-to-parent violence is a type of family violence in which children engage in violent behaviors against parents and both familial and non-familial caregivers. The present study aimed to analyze the relationship between child-to-parent violence and other manifestations of youth violence in a lower and upper secondary school population, comparing the incidence by gender among victims and aggressors, as well as the functions of the violence involved. Ninety-four students from a private school in the city of São Carlos (SP) participated, aged between 14 and 18 years (M=15.5; SD=0.99), with the majority (56.4%) being female. The results indicated a higher prevalence of psychological violence, followed by dominance/control behaviors and financial violence, with physical violence being the least frequent. It was also found that girls reported more violent behaviors of a reactive nature, especially against mothers. These findings reinforce the need to deepen studies on the family and social dynamics that influence the occurrence of child-to-parent violence, in order to support more effective prevention and intervention strategies in school and family contexts.
Child-to-parent violence from the perspective of adolescents
Keywords: Violência; Filho; Pais; Violence; Child; Parent; CIENCIAS HUMANAS::PSICOLOGIA; 3. Saúde e Bem-Estar